Energy method to calculate the density of liquids using ultrasonic reflection techniques - Higuti, Ricardo Tokio [UNESP]; Montero de Espinosa, Francisco R. [UNESP]; Adamowski, Julio Cezar [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2001)
In this work it is introduced a new approach to calculate the density of liquids in terms of the energies of the acoustic signals. This method is compared to other methods in the time domain (peak-to-peak amplitudes) and frequency domain magnitudes at a single frequency. It is used a measurement cell based on a multiple reflection technique, and it is developed an acoustic model for the cell. Simulations and experiments using several liquids are presented, showing that the energy method a less sensitive to noise than the other techniques. The relative errors in the density are smaller than 0.2% when compared to the values measured with a pycnometer.
Keywords: Acoustic impedance; Acoustic noise; Acoustic signal processing; Acoustic wave propagation; Acoustic wave reflection; Calculations; Computer simulation; Density of liquids; Frequency domain analysis; Mathematical models; Time domain analysis; Ultrasonic reflection; Acoustic model; Double element transducer; Energy method; Multiple reflection method; Ultrasonic applications